Ensino de história e projeto integrado : possibilidades para a geração de aprendizagens significativas no ensino médio - Bascheira, Deise Angélica Pasquali (My University, 2016)
This dissertation presents a directed research for History teaching in the High School and a work offer that favors learning through interdisciplinary projects, because it makes oneself respected which that methodology type puts young people and teachers before challenging educational practices. Objectives of this work: to examine the History discipline role in integrated projects, to analyze as they contribute to make the significant historical knowledge and to contribute to the thoughtful individuals training to their reality. The theme of this research is concern about the relevance of History classes for High School students. It investigates the integrated projects contribution, as an alternative to a significant learning in History, and the starting point is the experience analysis and presentation of a school. The sample consists of narratives from 88 students and two teachers involved with the project “Family Relations Ransom – where I live and where I came from”, fulfilled in 2011. For that analysis it chose itself the indicators perspective of a significant learning, presented by Seffner. It follows that the interdisciplinary activities break disciplines frontiers and defenses among people. For that, it is necessary attitude and posture interdisciplinary by teachers.
Esta dissertação apresenta uma pesquisa voltada ao ensino de História no Ensino Médio e uma proposta de trabalho que favorece a aprendizagem via projetos interdisciplinares, porque se acredita que esse tipo de metodologia coloca alunos e professores diante de práticas educativas desafiadoras. São objetivos deste trabalho: examinar o papel da disciplina de História nos projetos integrados, analisar como contribuem para tornar o conhecimento histórico significativo e colaborar para a formação de indivíduos atentos à sua realidade. O tema desta pesquisa é a preocupação com a relevância das aulas de História para alunos do Ensino Médio. Investiga a contribuição dos projetos integrados, como alternativa para uma aprendizagem significativa em História, e o ponto de partida é a apresentação e análise da experiência de uma escola. A amostra compreende narrativas de 88 alunos e dois professores envolvidos com o projeto “Resgate das Relações Familiares – onde vivo e de onde vim”, realizado em 2011. Para essa análise, escolheu-se a ótica dos indicadores de uma aprendizagem significativa, apresentados por Seffner. Conclui-se que a interdisciplinaridade rompe as fronteiras das disciplinas e os muros entre as pessoas. Para isso, é preciso atitude e postura interdisciplinares por parte dos professores.
Keywords: História - Estudo e ensino; História (Ensino médio); Aprendizagem; Abordagem interdisciplinar do conhecimento na educação; History - Study and teaching; History (High School); Learning; Interdisciplinary approach in education